The Anti-Inflammatory Benefit of Statins for Chronic Obstructive Pulmonary Disease (COPD): Review Article - Dewi, Yunita Kristiana (Pharmaceutical Journal of Indonesia, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is characterized by progressive, minimally reversible airflow limitation and systemic inflammation. Over the last 5 years, there have beenÂ  abundant studies proving the benefit of statin in COPD as an anti-inflammatory agent. So far, statin is mostly utilized in cardiology due to its effects of cholesterol reduction, immune system modulation, and anti oxidant. In point of fact, the effects of statin have proven to be advantageous when administered to COPD patients. The aim of this review is to examine the pharmacological mechanism of statins as anti-inflammatory drugs so that they can be considered as therapy in COPD.